Food Product Packaging Training for Entrepreneurs Fostered by the OKI Korkot - Hidayat, Ariodillah; Madalena, Mardalena; Andaiyani, Sri; Liliana, Liliana; Yunisvita, Yunisvita; Atiyatna, Dirta Pratama (Faculty of Economics, Universitas Sriwijaya, 2021)
Processed foods such as kemplang crackers, various chips, pempek etc. are commodity products produced by Entrepreneurs assisted by Korkot OKI, South Sumatra Province. The training will include training on introducing the concept of packaging, benefits of packaging, packaging design and making product packaging. This training is important because the processed food (kemplang, rengginang, chips, pempek) that is produced will certainly have added value if it is properly packaged. This packaging aims to maintain product quality, facilitate product distribution, and attract consumer attention. In implementing this packaging, all business participants do not have adequate packaging and do not have a product brand, so they will further provide assistance to design the training participants' brands and product packaging.